Provincial development of a patient-reported outcome initiative to guide patient care, quality improvement, and research. Issue 1 (January 2018) - Olson, Robert A.; Howard, Fuchsia; Lapointe, Vincent; Schellenberg, Devin; Nichol, Alan; Bowering, Gale; Curtis, Susan; Walter, Allison; Brown, Steven; Thompson, Corinne; Bergin, Jackie; Lomas, Sheri; et al.
The BC Cancer Agency Radiotherapy (RT) program started the Prospective Outcomes and Support Initiative (POSI) at all six centres to utilize patient-reported outcomes for immediate clinical care, quality improvement, and research. Patient-reported outcomes were collected at time of computed tomography simulation via tablet and 2 to 4 weeks post-RT via either tablet or over the phone by a registered nurse. From 2013 to 2016, patients were approached on 20, 150 attempts by POSI for patients treated with RT for bone metastases (52%), brain metastases (11%), lung cancer (17%), gynecological cancer (16%), head and neck cancer (2%), and other pilots (2%). The accrual rate for all encounters was 85% (n = 17, 101), with the accrual rate varying between the lowest and the highest accruing centre from 78% to 89% ( P < .001) and varying by tumour site ( P < .001). Using the POSI database, we have performed research and quality improvement initiatives that have changed practice.